The Impact of Microcredit on Child Education and Child Labor in Indonesian Microenterprise Households - Bayu Kharisma; Alfiah Hasanah; Siti Hudaepah (Universitas Negeri Semarang, 2025)
Microcredit is a financial instrument designed to improve well-being and reduced poverty rate. It also provides non-economic opportunities particularly in child education. This research aims to analyze the impact of microcredit participation from both formal and informal source on education and child labor in Indonesian Micro-Enterprise Households. This study utilizes data from the Indonesia Family Life Survey 5th wave in 2014/2015 and employs Propensity Score Matching model. The result shows that formal microcredit significantly raises school participation while reducing school gap. However informal microcredit does not show similar benefits on child education. The effect of child labor both from formal and informal microcredit remain inconclusive, highlight the need for further research that account for potential confounding factors. This finding suggests policymakers to prioritize access to formal microcredit especially for micro-enterprise households.